Dynamism vs Stability of Sociocultural Stereotypes - Lyubymova, Svitlana; Shutova, Maria (2024)
Focusing on the dynamic nature of sociocultural stereotypes, we examine changes in linguistic representation of the hipster stereotype, which is considered a verbalized cognitive structure that embodies a simplified and conventional image of a social group. The study is based on the premise that dynamism of a sociocultural stereotype can be detected and described mainly by linguistic methods and techniques that include semantic, motivational, distributional, contextual analysis. Notable alterations of verbalized sociocultural stereotypes are observed in media discourse, which is highly responsive to social processes that influence stereotyping. The data for the study is collected from American web-based digital sources and language corpora. The results of the research confirm linguistic representation of sociocultural stereotypes is a dynamic process of their formation, functioning and changing that comprise qualitative and quotative transformations. Qualitative changes are transformations of the stereotype characteristics, represented by lexical items and syntactic units. Quantitative changes concern the increase or reduction in frequency of the sociocultural stereotype in media discourse with subsequent disappearance of it. Under certain conditions, the disappeared sociocultural stereotype renews in media discourse. The results of our research can be of use in a wide range of linguistic studies aimed at detecting changes in verbalized cognitive units.
Keywords: sociocultural stereotype; subcultural group; hipster; media stereotyping; dynamism